Specificity of the human IgE response to inhaled acid anhydrides. - Topping, MD; Venables, K; Luczynska, C; Howe, W; Taylor, A (1986)
Patients with work-related respiratory symptoms caused by inhaled acid anhydrides (trimellitic (TMA), phthalic (PA), tetrachlorophthalic (TCPA), and maleic anhydrides) have specific IgE antibody. The antibody is specific for a conjugate of the sensitizing anhydride (the hapten) and human serum albumin (HSA). We have investigated the specificity of the reaction to determine whether the antibody is directed against (1) the anhydride, (2) new antigenic determinants formed by conjugation of albumin with the anhydride, or (3) the complete anhydride-HSA conjugate. For the patients sensitized to TCPA and TMA, RAST inhibition studies demonstrate the anhydride-HSA conjugate to be a more effective inhibitor of RAST than the sodium salt of the anhydride or an anhydride-bovine serum albumin conjugate, whereas for those sensitized to PA, the free hapten is almost as an effective inhibitor as the conjugate. With each sera HSA conjugates of anhydrides to which the patient is not sensitized are weaker inhibitors than the sensitizing anhydride-albumin conjugate. These results provide strong evidence that for the patients sensitized to TCPA and TMA, the antibody combines with the anhydride and the spatially adjacent portion of the HSA molecule, whereas in the patients sensitized to PA, the antibody is specific for the hapten.